Reporting Some Case Studies Concerning Information and Communication Technology Based Inclusion into University - Pepino, Alessandro; Sicignano, Gennaro; Torri, Adriano (New Ideas Concerning Science and Technology Vol. 4, 2021)
In recent years, a revolution occurs, in both the school and the university: the traditional education paradigms have been questioned. This phenomenon has been triggered by two phenomenon: the use of new information and communication technology-based learning paradigms by the students; the growing focus on the needs of inclusion of students with disabilities and specific learning disabilities. This paper discusses some examples in which we not only explain how ICT serves to help students with special needs to integrate within the university context, but also how a multidisciplinary approach in the management of inclusion projects allows you to better manage this type of projects and improve the lives of the students involved.